2017
DOI: 10.1186/s12913-017-2276-2
|View full text |Cite
|
Sign up to set email alerts
|

Health literacy and primary health care use of ethnic minorities in the Netherlands

Abstract: BackgroundIn the Netherlands, ethnic minority populations visit their general practitioner (GP) more often than the indigenous population. An explanation for this association is lacking. Recently, health literacy is suggested as a possible explaining mechanism. Internationally, associations between health literacy and health care use, and between ethnicity and health literacy have been studied separately, but, so far, have not been linked to each other. In the Netherlands, some expectations have been expressed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
29
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 30 publications
4
29
0
4
Order By: Relevance
“…Age and country of birth have previously shown strong associations with multiple scales of the HLQ in Australian study populations [ 9 , 10 , 41 ]. However, our current study showed smaller ES and associations in fewer health literacy scales for both of these sociodemographic characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Age and country of birth have previously shown strong associations with multiple scales of the HLQ in Australian study populations [ 9 , 10 , 41 ]. However, our current study showed smaller ES and associations in fewer health literacy scales for both of these sociodemographic characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…More frequent medical visits among people with higher SES may be due to their greater health competence, better knowledge of alarming symptoms, or better ability to use the system. However, evidence from other countries shows that a higher level of health competence is not related with the frequency of use of the health care system or that the association is inverse [17][18][19][20][21]; nor were the higher competences predictive of medical assistance overuse [22]. More frequent medical visits in Poles with high SES may indicate that the better availability of the health care system was related to a better financial situation.…”
Section: Discussionmentioning
confidence: 99%
“…One possible explanation for our findings is that perceived high-quality primary health-care services provides participants with a strong sense of security, preparedness and belonging, which may compensate for other disadvantages associated with living in a small town. There is evidence to suggest that primary health-care services play a key role in social, political, and international community development, particularly in low-income minority groups [ 62 , 63 ]. Several studies in minority populations, including Arabs in Israel, have shown that minority groups tend to use primary health-care services more often than non-minority ones, partly due to health literacy [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence to suggest that primary health-care services play a key role in social, political, and international community development, particularly in low-income minority groups [ 62 , 63 ]. Several studies in minority populations, including Arabs in Israel, have shown that minority groups tend to use primary health-care services more often than non-minority ones, partly due to health literacy [ 62 ]. For example, a recent Israeli study indicated that Arabs have reported receiving health promotion advice (e.g., physical activity, diet) from their primary doctor more commonly than Jewish patients [ 64 ].…”
Section: Discussionmentioning
confidence: 99%